2022
DOI: 10.3389/fonc.2022.860563
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Co-Mutations in Advanced EGFR-Mutated Non–Small Cell Lung Cancer: Prognosis and Therapeutic Strategy for Cancer Therapy

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. As the most prevalent molecular mutation subtypes in non-small cell lung cancer (NSCLC), EGFR-TKIs are currently a standard first-line therapy for targeting the mutated EGFR in advanced NSCLC patients. However, 20-30% of this subset of patients shows primary resistance to EGFR-TKIs. Patients with co-mutations of EGFR and several other genes have a poor response to EGFR-TKIs, whereas the prognostic and predictive significance of EGFR/TP53 co-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 108 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…Also, there is no current research claiming that p53 mutations are solely the critical molecular drivers of wild‐type NSCLC. Rather many studies have reported that NSCLC patients (with mutant or wild‐type EGFR tumors) harboring p53 mutations generally have increased rates of resistance to chemotherapy or EGFR TKIs (Jung et al, 2021; Liu et al, 2022). Cell cycle analysis studies were performed and showed that a significant G1 phase cell cycle arrest (Figure 2) induced by MMA307 and MMA320 treatment against NCI‐H226 cells offers support to the idea that these compounds inhibit cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Also, there is no current research claiming that p53 mutations are solely the critical molecular drivers of wild‐type NSCLC. Rather many studies have reported that NSCLC patients (with mutant or wild‐type EGFR tumors) harboring p53 mutations generally have increased rates of resistance to chemotherapy or EGFR TKIs (Jung et al, 2021; Liu et al, 2022). Cell cycle analysis studies were performed and showed that a significant G1 phase cell cycle arrest (Figure 2) induced by MMA307 and MMA320 treatment against NCI‐H226 cells offers support to the idea that these compounds inhibit cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…We also characterized the mutational profile of the RET-rearranged patients and found that TP53 was the most common concurrent alteration. Previous studies have suggested that TP53 concomitant mutations have a strong negative effect on the outcomes of patients with EGFRmutant (42)(43)(44)(45) and ALK-rearranged NSCLC (43,46,47). The poor prognostic effect of the TP53 mutation on tumors may be due to the loss of tumor inhibitory function and the elevated level of genomic instability (48).…”
Section: Discussionmentioning
confidence: 99%
“…To identify biomarkers that predict the development of T790M resistance mutations, we evaluated a multitude of complex biomarkers based on the WES data of both patient groups (Figure 2). NSCLC is known to harbor TP53 comutations [30], which we identified belonging to pathogenic and likely pathogenic categories in 21 cases (54% of the cohort patients, 48% in T790Mpos, and 64% in T790Mneg), yet they did not display a significant difference between both groups (Figure 2 and supplementary material, Table S2). While there were several other mutations present in both groups, we did not identify statistically significant differences for any mutation between T790Mpos and T790Mneg cases (supplementary material, Table S3).…”
Section: Resultsmentioning
confidence: 99%